RUMAH SUSUN DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN DI MANGGARAI, JAKARTA SELATAN - Yusniarti Apriza; Tri Joko Daryanto; Amin Sumadyo (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Vertical Housing still become the solution of fulfilling housing needs as dense and slum settlement spread, such as in Manggarai, South Jakarta. Vertical Housing which had been built in Jakarta which had to do a fast construction sometimes ignore the social and economic factors of occupants, as well as the impact of construction to environment. Therefore, the construction of Vertical Housing has to integrate the social, economic, and environmental factor. The problem of design is how to design a form of building such as space and building façade which able to facilitate activities and occupants’ need which is affected by site conditions and social life of occupants. This Vertical Housing aims to get spaces for activities and fulfilling the needs of occupants in the present and the future, and minimizing negative impacts of construction to environment. Design methode based on the concept of Sustainable Architecture because it considers the balancing of social, economic and environmental factors. The implementation of Sustainable Architecture is done by applying five Sustainable Architecture chosen aspects, such as sustainable site and land-use, sustainable energy, sustainable material, sustainable water, and sustainable community. These design aspects of Sustainable Architecture will result some concepts such as provision of shared social and economy spaces, green open spaces, the use of durable and eco-friendly materials, building façade responds to climate, and waste treatment system. Keywords: Economic, Environment, Social, Sustainable Architecture, Vertical Housing